MOLECULAR MODELING OF WATER STRUCTURE IN NANO-PORES BETWEEN BRUCITE (001) SURFACES - Wang J.; Kalinichev A.G.; Kirkpatrick R.J. (My University, 2004)
Molecular dynamics,(MD) computer,simulations of liquid water held in one-dimensional nano- confinement by two parallel, electrostatically neutral but hydrophilic surfaces of brucite, Mg(OH) 2, provide greatly increased, atomistically detailed understanding of surface-related effects on the spatial variation in the structural ordering, hydrogen bond (H-bond) organization, and local density of H2O molecules at this important model hydroxide surface. NVT-ensemble MD simulations (i.e., at constant number of atoms, volume and temperature) were performed,for a series of model,systems consisting of 3 to 30 A û -thick water layers (containing 35 to 360 H2O molecules) confined between,two 19 A û -thick brucite substrate layers. The results show that the hydrophilic substrate significantly influences the near-surface water structure, with both H-bond donation to the surface oxygen,atoms and H-bond acceptance from the surface hydrogen,atoms in the first surface layer of H2O molecules playing key roles. Profiles of oxygen,and hydrogen,atomic density and H 2O dipole orientation show,significant deviation from the corresponding,structural properties of bulk water to distances as large as 15 A û (5 molecular water layers) from the surface, with the local structural environment varying significantly with the distance from the surface. The water molecules,in the first layer at about 2.45 A û from the surface have a two-dimensional hexagonal arrangement parallel to brucite layers, reflecting the brucite surface structure, have total nearest neighbor coordinations of 5 or 6, and are significantly limited in their position and orientation. The greatest degree of the tetrahedral (ice-like) ordering occurs at about 4 A û from the surface. The translational and orientational ordering of H 2O molecules,in layers further from the surface become,progressively more similar to those of bulk liquid water. A quantitative statistical analysis of the MD-generated instantaneous molecular configurations in terms of local density, molecular orientation, nearest neighbor coordination, and the structural details of the H-bonding network shows that the local structure of interfacial water at the brucite surface results from a combination,of “hard wall” (geometric and confinement) effects, highly directional H-bonding, and thermal motion. This structure does not resemble that of bulk water at ambient conditions or at elevated or reduced temperature, but shares some similarities with that of water under higher pressure.